Ultrasonographic, computed tomographic, and operative findings in dogs infested with giant kidney worms (Dioctophyme renale) - Rahal, Sheila Canevese [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Oliveira, Hugo S. [UNESP]; Mesquita, Luciane R. [UNESP]; Faria, Luis G. [UNESP]; Takahira, Regina Kiomi [UNESP]; Matsubara, Lidia M. [UNESP]; Agostinho, Felipe S. [UNESP] (Amer Veterinary Medical Assoc, 2014)
Objective To compare ultrasonographic, CT, and surgical findings in dogs infested with giant kidney worms (Dioctophyme renale).Design-Case series.Animals-15 crossbred dogs infected with D renale.Procedures-Immediately after ultrasonography was performed with dogs in dorsal recumbency, sequential transverse images of the abdomen were acquired with a helical CT scanner. After plain CT, contrast CT was performed with a nonionic iodinated contrast agent. Subsequently, exploratory celiotomy was performed.Results-In the corticomedullary area of the right kidney of 12 dogs, ultrasonography revealed several ring-like structures with an echogenic wall and anechoic central area in the transverse plane and arrayed as bands in the longitudinal plane. Similar structures were observed in the abdominal cavity of 10 dogs. In 13 dogs, CT revealed loss of corticomedullary differentiation in the right kidney, with discrete uptake of contrast material in the periphery of the kidney, and several ring-like or elongated structures with a hyperdense wall and hypodense center. In 11 dogs, the same structures were observed free in the abdominal cavity. Surgery revealed that 13 dogs had a damaged right kidney that required nephrectomy. Parasites were found free in the abdominal cavity of 7 dogs.Conclusions and Clinical Relevance-Ultrasonography and CT were effective imaging methods for detecting D renale in the kidney and less effective for detecting parasites in the abdominal cavity. Care should be taken to avoid erroneously interpreting normal structures as parasites, especially in the abdominal cavity.